Fluid balance during team sports - Burke, L. M. (Journal of Sports Sciences, 1997)
Sweat losses during team sports are influenced by the intermittent nature of the work rates (high-intensity exercise interspersed with low-level activity and both formal and informal rest periods), and a high level of inter- and intra-individual variability in workloads. Since many team sports have evolved in countries with cool climates, traditions and rules governing the time of play, duration of play without a break, and the type of uniforms may lead to inappropriately high thermal stresses when these sports are played in hot environments (i.e. >25°C, 60% relative humidity). Fluid intake during team sports is largely determined by opportunities to drink during formal rest periods and during informal stoppages in play. Present regulations concerning fluid breaks in some sports may be inappropriate if fluid requirements of players competing in hot environments are to be met to prevent hypohydration and fatigue. Nevertheless, it appears that in most team sports, there are adequate opportunities for players to keep fluid deficits below 2% of body mass. Studies across a number of sports show that mean fluid intakes of up to 1000 ml h-1 can be achieved. Strategies are required to help team sport players realize the importance of optimal hydration, and to use or create opportunities within their sport to maximize fluid intake. Guidelines for hydration during training and competition are suggested with the proviso that these should be adapted for each individual and his or her own sport.